Experimental and computational study of thermal energy storage with encapsulated NaNO3 for high temperature applications. (May 2015) - Zheng, Ying; Barton, John L.; Tuzla, Kemal; Chen, John C.; Neti, Sudhakar; Oztekin, Alparslan; Misiolek, Wojciech Z.
Highlights: Thermal energy storage using EPCM is experimentally investigated. Encapsulated NaNO3 is shown to work repeatedly for energy storage and retrieval. In a pilot facility, it is shown that the encapsulated NaNO3 can store ∼451 kJ/kg thermal energy when heated from ∼20 °C to ∼400 °C. A simulation model has been developed for the EPCM based TES System. Numerical predictions have shown good agreements with experimental data. Abstract: The objective of this work is to establish methods for storage of thermal energy using encapsulated phase change materials (EPCMs) at temperatures up to 440 °C applicable in concentrating solar plants (CSPs), in which heat transfer fluid (HTF) from the solar collector would pass through the storage system embedded with EPCM capsules. NaNO3, having latent heat of 176 kJ/kg at 308 °C, is selected as the storage medium. Stainless steel capsules containing NaNO3 are fabricated and installed in a pilot-scale thermal energy storage (TES) system for performance tests. Compressed air is used as heat transfer fluid in the current tests. The test section (T/S) with EPCM capsules successfully demonstrate the ability to transfer thermal energy to and from a transport fluid, achieving energy storage and retrieval in multiple charging and discharging cycles. In a given cycle where capsule temperatures varied from ∼250 °C to ∼386 °C, the EPCM is found to store significant energy per unit mass (∼211 kJ/kg of capsule), with the phase change material (PCM) NaNO3 accounting for ∼95% of the total energy stored in the capsules. The latent heat of the NaNO3 contributes to ∼42% of the energy stored in the capsules. It is expected that the storage density of the EPCM would be even greater for plant size TES systems with larger size capsules, without the penalties associated with the limited scale used here. A mathematical model has been developed for the test section with EPCM capsules and its predictions are found to agree with experimental measurements within 7% discrepancy in stored energy. The dynamic performance of charging and discharging rates are also well predicted by the model, giving confidence for engineering design capabilities in future applications using EPCMs for thermal energy storage.